Teknik Cognitive Restructuring Dalam Konseling: Mengubah Pola Pikir Negatif Menjadi Positif Melalui Pendekatan Literatur - Sabila Sofiannisa; Riffati Hikmi Mori; Fania Halisa Lisbeth; Imalatul Khairat (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study systematically reviews empirical evidence examining the effectiveness of Cognitive Restructuring techniques in counseling across diverse educational and psychosocial contexts. Findings demonstrate that this approach effectively addresses various psychological issues, including anxiety, body shame, academic stressors, and low self-esteem. The analysis reveals five key cognitive-emotional domains impacted: (1) negative automatic thoughts, (2) cognitive distortions, (3) emotional regulation, (4) self-image, and (5) intrinsic motivation. Importantly, the technique not only reduces psychological symptoms but also enhances social functioning, academic participation, and adaptive behaviors. Practical applications include thought journals, Socratic dialogues, and ABCDE frameworks, all showing measurable improvements in clients' rational thinking and coping strategies. The review concludes that Cognitive Restructuring's efficacy depends on both systematic implementation and counselor competence in guiding cognitive reflection. These findings establish it as an evidence-based intervention for mental health enhancement and maladaptive thought modification in counseling practice.